2011
DOI: 10.1210/jc.2010-1054
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Nonfunctioning Pituitary Adenomas and Incidentalomas: A Systematic Review and Metaanalysis

Abstract: Despite the relatively high prevalence of PIs/NFPAs, the evidence on the natural history of these entities is scarce and of low quality. PIs/NFPAs seem to have fairly rare complications that may be more common when lesions are large (>10 mm) and solid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
142
5
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 25 publications
7
142
5
14
Order By: Relevance
“…However, by reviewing the literature on the natural history of untreated symptomatic NFPA and incidentally discovered NFPA, the rate of tumor growth during the follow-up period ranged from 7 to 50% (3,4,5,6,8,9,19,33,34,35). Furthermore, in their metaanalysis Fernández-Balsells et al (17) estimated that during the follow-up the tendency of tumor growth was 12.5% per year (95% CI 7.9-17.2%), the risk of new endocrine dysfunction was 2.4% per year (95% CI 0.0-6.4%), and the risk of worsening of the visual field was 0.65% per year (95% CI 0.47-0.82%). Therefore, our results can reassure patients who choose surgical removal of asymptomatic and incidentally discovered NFPA that early and late outcome is very good at the expense of minimal risks of the surgical procedure, including a low risk of developing new pituitary deficiencies.…”
Section: Surgery For Pituitary Incidentalomasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by reviewing the literature on the natural history of untreated symptomatic NFPA and incidentally discovered NFPA, the rate of tumor growth during the follow-up period ranged from 7 to 50% (3,4,5,6,8,9,19,33,34,35). Furthermore, in their metaanalysis Fernández-Balsells et al (17) estimated that during the follow-up the tendency of tumor growth was 12.5% per year (95% CI 7.9-17.2%), the risk of new endocrine dysfunction was 2.4% per year (95% CI 0.0-6.4%), and the risk of worsening of the visual field was 0.65% per year (95% CI 0.47-0.82%). Therefore, our results can reassure patients who choose surgical removal of asymptomatic and incidentally discovered NFPA that early and late outcome is very good at the expense of minimal risks of the surgical procedure, including a low risk of developing new pituitary deficiencies.…”
Section: Surgery For Pituitary Incidentalomasmentioning
confidence: 99%
“…Surgery is usually advised also in asymptomatic patients with tumors that abut the optic chiasm (15). In older patients without visual deficit, a more conservative approach might be preferred (16,17). Even in patients with asymptomatic NFPA, immediate surgery might be considered, but most authors recommend clinical and neuroradiological follow-up as first option (15,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…9,22,34,43,46,48 In a recent metaanalysis of the natural history of nonfunctioning pituitary adenomas, the incidence of growth in macroadenomas was reportedly 12.53 per 100 person-years. 18 Two years prior, O'Sullivan et al found that 33.5% of 159 patients with nonfunctioning adenomas who underwent resection, but not postoperative radiation therapy or radiosurgery, demonstrated evidence of recurrence or growth at a median follow-up of 4.1 years (range 1-20.7 months). The 5-and 10-year actuarial rates of recurrence or growth of residual adenoma were 24.4% and 51.5%, respectively.…”
mentioning
confidence: 99%
“…Diagnosis is usually established by detecting the predominant complications of neurological character, perhaps some degree of hypopituitarism, headache, and other clinical manifestations induced by the unpredictable biological behavior of those tumors. Prevalence of specific cellular lineage varies, but is has been calculated to be as 7 to 9 cases out of 100,000 inhabitants, including the silent gonadotrope, corticotrope, thyrotrope, oncocytic, null cell, lactotrope, and other silent cellular lineages [4,9]. In contrast to these data, a higher prevalence was registered in Belgium with a figure of 94 patients out of 100,000 people [10].…”
Section: Introductionmentioning
confidence: 97%
“…An early diagnosis is obtained in the case of female patients [5] as reported by Nabarro [6]. The non-functioning pituitary adenomas are a heterogeneous subset of neoplasms of monoclonal origin of the adenohypophysis [7], which constitute 25-30% of pituitary neoplasias [8,9]. Diagnosis is usually established by detecting the predominant complications of neurological character, perhaps some degree of hypopituitarism, headache, and other clinical manifestations induced by the unpredictable biological behavior of those tumors.…”
Section: Introductionmentioning
confidence: 99%